The effect of low-dose esketamine on maternal depression after cesarean delivery - Yan Shang; Siyuan Li; Qin Zheng; Tingting Mi; Yuzhu Lv; Lichun Han; Binrong Wang (Journal of Psychosomatic Obstetrics and Gynecology)
Objective To assess the impact of low-dose intravenous esketamine on postpartum depression scores in women undergoing cesarean section.Methods In a randomized, double-blind, placebo-controlled trial, 186 women aged 20–50 years receiving epidural anesthesia for cesarean section were divided into three groups: Group A (0.25 mg/kg esketamine intraoperatively + esketamine in PCIA), Group B (0.25 mg/kg esketamine intraoperatively + PCIA without esketamine), and Group C (placebo intraoperatively + PCIA without esketamine). The primary outcome was the change in Edinburgh Postnatal Depression Scale (EPDS) scores. Secondary outcomes included Pittsburgh Sleep Quality Index (PSQI) scores, Visual Analogue Scale (VAS) scores, PCIA bolus frequency, and adverse events.Results EPDS and PSQI scores decreased significantly post-surgery across all groups (p < 0.05). Groups A and B showed greater EPDS score reductions than Group C at 5, 7 and 14 days postoperatively (p < 0.01). No significant differences were observed in PSQI scores, VAS scores or PCIA bolus frequency between groups. Adverse events though mild and transient, were more frequent in Group A (p < 0.01).Conclusion Low-dose intravenous esketamine, reduces postpartum depression scores post-cesarean section, with a safe profile despite increased mild adverse events when combined with PCIA.